Colonial Catharsis: Romantic-Realism and the Imperial Gaze in Confessions of a Thug - Kevin Frank (Humanities)
This article is situated in the context of Victorian imaginations saturated with stories of crime and punishment and influenced by Romantic horror and terror aesthetics involving the sublime. The author delineates how the novel’s realism is affixed to an inherent romanticism and argues that the affect and effect of terror and horror resulting from colonial crimes exhibited in the novel allow readers to experience catharsis and to reassert their humanity through the imperial gaze. Additionally, readers may confirm the values of the ‘home’ nation and the justification of British colonisation through the trope of ‘bringing order out of chaos’.